Effect of climate change on agricultural productivity: A case study of Nigeria - Sikwela, Misery Mpuzu; Aderemi, Timothy Ayomitunde (Asian Journal of Agriculture and Rural Development, 2025)
Over the time, the escalating buildup of greenhouse gases in the atmosphere has been altering the distribution of precipitation, elevating temperatures, stimulating more frequent instances of severe weather events, and causing shifts in the timing of growing seasons. However, in the Nigerian context, it is worth noting that the agricultural sector, along with its agro-allied industries, holds significant potential to stimulate economic growth and foster diversification away from reliance on crude oil. Against this backdrop, this study examined the impact of climate change on agricultural productivity in Nigeria. The study reveals that climate change variables have a positive impact on agricultural productivity in the country. Based on the findings of the analysis, the efficacy of managing the ongoing fluctuations in climatic variables can be modestly enhanced through the implementation of government policies that prioritize mitigation measures.